Quantum Cooperative Multicast in a Quantum Hybrid Topology Network - Chen, Si-Yi; Xu, Gang; Chen, Xiu-Bo; Shang, Tao; Yang, Yi-Xian (Frontiers in Physics, 2022)
Quantum multicast is a significant transmission mode in multi-party communication scenario. Multi-sources collaboration can further enhance the efficient multicast. However, it remains a challenge to realize quantum multicast with a cooperative way in complex topology network. In this paper, we propose a scheme of quantum cooperative multicast in a hybrid topology network. It provides information aggregation and simultaneous multipoint transmission services. Firstly, collaborative information aggregation allows central network data to be integrated into the aggregation node. By exploiting quantum multicast mode, the aggregation node can simultaneously deliver integrated quantum states to multi targets. Secondly, our scheme is feasible for dynamic network expansion. It is capable of extending network architecture iteratively, while the peer network requests can be handled in parallel. Finally, the new scheme shows great application potential in the distributed quantum network. It is a promising candidate for the implementation of quantum data disaster backup in future.